Exploring urban space quantitative indicators associated with outdoor ventilation potential. (April 2022) - Li, Jiaying; You, Wei; Ding, Wowo
Highlights: Explores an urban form indicator associated with local outdoor ventilation potentials. Provides a method for the correlation study between urban space form and regional spatial ventilation condition based on spatial partition. Space partition method is an important factor that affects the degree of correlation between the SVF and ventilation index. SVF could be an urban form parameter related to urban spatial ventilation for urban space. Abstract: Urban ventilation conditions, which are significantly influenced by urban space forms, are essential for healthy and livable urban environments. In urban design practice, morphological indicators related to urban ventilation could be improved for the effective assessment of ventilation quality and timely adjustment of the design. This study attempted to explore local spatial morphological indicators related to ventilation performance. Considering the sky view factor ( SVF ) as a quantitative parameter of urban local spaces, this study investigated the correlation between the SVF and outdoor ventilation performance. The SVF was calculated using single and multipoint methods, and a wind velocity ratio was adopted as the spatial ventilation performance indicator. In addition, local spaces were defined using three different partition methods (GSP1, GSP2, and CSP), as the urban space is continuous and complex. A typical urban centre space in Nanjing, China, was adopted as the research subject. The wind flows were calculated using the computational fluid dynamics (CFD) method for two wind directions. The results showed a positive correlation between the SVF and ventilation indices. Different partitioning methods had a considerable impact on the correlation, as the value of R 2 between SVF and could reach around 0.3 in GSP1 and CSP but only 0.05 in GSP2.